A Semantic Analysis of the Collocative Meaning of Ta?awwul in Qatar’s Third National Development Strategy 2024–2030 - Naufal Pratama Putra; Letmiros Letmiros (Mahesa Research Center, 2026)
This study examines the collocative meaning of the word ????? /ta?awwul/ in the Third Qatar National Development Strategy 2024–2030 document. The word ????? frequently appears in official policy documents and development discourse in Gulf countries, including Qatar. However, the term is polysemous and cannot be fully understood through its lexical meaning alone, as it is used across various contexts, such as economics, bureaucracy, and others. Therefore, this study aims to identify variations in the collocation patterns of the word ????? and explain how these variations form different collocative meanings in the document. This study uses a qualitative method with a semantic approach based on Benson's collocation theory (1986) and Akasyah's contextual expression meaning theory (2011). The findings reveal that ????? appears 10 times in the document and forms three distinct collocational patterns: ?ifah + maw??f occurring three times, ma?dar + ?arf jar occurring six times, and mu??f + mu??f ilayh occurring once. From these variations in collocational relationships, two contextual meanings of ????? emerge: ‘transition,’ referring to an external shift toward a new condition or orientation in the contexts of modernization, economy, and energy; and ‘transformation,’ referring to an internal, fundamental, and comprehensive change in the contexts of development, technology, labor, and governance. These findings confirm the relevance of Benson’s collocation theory and Akasyah’s contextual expression meaning theory in the analysis of national development strategy documents of Arab countries, particularly Qatar, and demonstrate how the choice of collocational patterns plays a role in shaping the meanings represented in these documents.